Mt. Etna Feeding System and Sliding Flank: A New 3D Image From Earthquakes Distribution in a Customisable GIS - Guardo, R.; De Siena, L.; Dreidemie, C. (Frontiers in Earth Science, 2020)
High-resolution seismic imaging enables the reconstruction of ascending paths of magma and fluids, shallow molten accumulation and flank collapse areas, all crucial information for developing an efficient eruption forecasting strategy. Here, the Marching Cubes algorithm (MC - generally applied to medical visualization and three-dimensional (3D) modeling) is applied to 16 years of earthquake location data at Mt. Etna (Italy). The algorithm defines three-dimensional seismic clusters that take into account seismic location uncertainties and are embedded in a novel volcano-oriented Geographyc Information Systems (VolGIS) offering an interpretational environment comprising tomographic images and alternative geophysical models. The results show that a volume of very-low-seismicity is embedded in a high-velocity body, and acts as a zone of transition between transient magmatic events (west) and eastern deep seismicity related to the sliding eastern flank. The eastern cluster represents the 3D seismic signature of a deep (2–8 km below sea level) instability, affecting the portion of the eastern flank nearest to the feeding systems. This instability is likely caused by a combination of gravitational spreading and magmatic intrusions.